2003
DOI: 10.1046/j.1365-2958.2003.03624.x
|View full text |Cite
|
Sign up to set email alerts
|

Distant cis‐active sequences and sialic acid control the expression of fimB in Escherichia coli K‐12

Abstract: SummaryThe phase variation of type 1 fimbriation in Escherichia coli is controlled by the inversion of a 314 bp element of DNA, determined by FimB (switching in both directions) or FimE (switching from the ON-to-OFF orientation predominantly), and influenced by auxiliary factors IHF, Lrp and H-NS. The fimB gene is separated from the divergently transcribed yjhATS operon by a large (1.4 kbp) intergenic region of unknown function. Here, we show that fimB expression is regulated by multiple cis-active sequences t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
89
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(98 citation statements)
references
References 58 publications
8
89
1
Order By: Relevance
“…GlcNAc-6-P is further metabolized to fructose-6-phosphate by NagA and NagB, two enzymes of the N-acetylglucosamine (GlcNAc) degradation pathway, whose synthesis is controlled by the nagC-encoded repressor (10,20). Neu5Ac regulates transcription of fimB, and it has been suggested that it could also control the expression of the divergently expressed yjhATS operon (7,29). We show in this work that yjhA is indeed regulated by NanR and several other regulators and that it encodes a Neu5Ac-specific channel.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…GlcNAc-6-P is further metabolized to fructose-6-phosphate by NagA and NagB, two enzymes of the N-acetylglucosamine (GlcNAc) degradation pathway, whose synthesis is controlled by the nagC-encoded repressor (10,20). Neu5Ac regulates transcription of fimB, and it has been suggested that it could also control the expression of the divergently expressed yjhATS operon (7,29). We show in this work that yjhA is indeed regulated by NanR and several other regulators and that it encodes a Neu5Ac-specific channel.…”
supporting
confidence: 54%
“…fimB expression is regulated by Neu5Ac through the binding of the NanR regulator at a specific site in the fimB-yjhA intergenic region (Fig. 1A) (7,27). To verify whether NanR could also control yjhA expression, we measured expression of a yjhA-lacZ fusion in the absence and presence of Neu5Ac.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase variation of fim is associated with inversion of a short (Ϸ300 bp) DNA element that contains a promoter for the structural genes (18,19). Inversion of the fim element involves two tyrosine family recombinase proteins, FimB and FimE, and is subject to elaborate control producing both (i) a relatively low frequency of switching from the afimbriate (off) to fimbriate (on) phase (between 10 Ϫ4 and 10 Ϫ3 per cell per generation), and (ii) control by environmental signals, including temperature, the branched-chain amino acids (particularly leucine) and alanine, and Neu 5 Ac (20)(21)(22). Whereas the amino acids stimulate fim phase variation in both directions, Neu 5 Ac inhibits switching from the off to on phase specifically (21,22).…”
mentioning
confidence: 99%
“…Whereas the amino acids stimulate fim phase variation in both directions, Neu 5 Ac inhibits switching from the off to on phase specifically (21,22). Neu 5 Ac inhibits fimB expression, and thus exerts a selective effect on the inversion by inhibiting FimB, but not FimE, recombination (21).…”
mentioning
confidence: 99%